Anticancer studies of crude extract and essential oil from Eugenia aromaticum / Wan Nor I’zzah Wan Mohamad Zain, Gabriele Anisah Ruth Froemming and Mohammad Johari Ibahim - Wan Mohamad Zain, Wan Nor I’zzah; Froemming, Gabriele Anisah Ruth; Ibahim, Mohammad Johari (2009)
Spices are the source of antioxidants, which prevent the oxidative stress caused by the reduction process of oxygen that leads to DNA damage and several diseases inclusive of cancer. Therefore they represent a potential source of new compounds with anticancer and antioxidant properties. Methanol crude extract and essential oil isolated from Eugenia aromaticum or clove, were investigated for anticancer and antioxidant activities. The essential oil which was obtained by hydrodistillation and analysed using GC-MS was mainly made up of isoeugenol (62.11%), followed by caryophyllene (14.54%), isoeugenol acetate (5.40%), octasane (2.43%), a-humulene (2.22%), triacontane (1.95%), octadecane (1.66%), nonacosane (1.40%), octacosane (1.38%), and hexacosane (1.35%). The effect of methanol crude extract and essential oil against four human cancer cell lines: HepG2 (hepatic cancer), MCF-7 (hormone-dependent breast cancer), MDA-MB-231 (non-hormone-dependent breast cancer), and HeLa (cervical cancer) and normal cells; 3T3 was measured using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. It was shown that both the methanolic extract and essential oil inhibited 50% cancer cells growth at the concentrations > 100 ug/ml. However, tamoxifen (control positive) inhibited 50% cancer cells at the concentrations < 15 ug/ml. Effect could also be seen on normal cells growth. Among all cancer cell lines tested, both E. aromaticum methanolic extract and essential oil were more effective in inhibiting MCF-7 estrogen dependent breast cancer cell line. Thus, the growth inhibitory effect of the sample was measured which illustrated that E. aromaticum methanolic extract did not inhibit the cancer cells growth rate but it caused the shrinkage of the cells. The results were similar to tamoxifen.